EFFECTS OF FINANCE COST ON THE PROFITABILITY OF LISTED MINING FIRMS IN NIGERIA (Journal of Contemporary Issues in Accounting, 2022)
This study focused on the effect of finance costs on the profitability of listed mining firms in Nigeria. The study was prompted because of the burden of debt via interest cost in discouraging investment in the Nigerian mining industry. Thus, the study determined the effect of the finance cost ratio (FCR) on the return on asset (ROA) of listed mining firms in Nigeria and the effect of the interest coverage ratio (ICR) on the return on equity (ROE) of listed mining firms in Nigeria. The study answered four research questions and tested four hypotheses. Secondary data was used for the execution of this research work with an ex-post facto research design. Data extracted from the financial statement of a listed mining firm in the Nigeria Exchange Group (NGX) were analyzed using the regression analysis statistical tool with the aid of Statistical Package for Social Science (SPSS) Version 22.0. The result of the analyses carried out show that the financial cost ratio (FCR) has a positive and significant effect on the return on asset (ROA) of listed mining firms in Nigeria. It also revealed that the interest coverage ratio (ICR) has a negative and non-significant effect on return on equity (ROE). It was therefore recommended amongst others that companies should use their internal financing resources as far as possible to mitigate the effect of excessive interest cost on the profitability of the firms and that government should create a good business environment by regulating the levels of interest rates and thus making it easy for mining firms to access debt finance with lower cost implications.
Keywords: Profitability; Return on Equity; Return on Asset; Finance Cost; Mining; Royalty; Exploration